Comparison of TRUS and combined MRI-targeted plus systematic prostate biopsy for the concordance between biopsy and radical prostatectomy pathology - (:unkn) unknown (WILEY, 2021)
Aim: To evaluate the accuracy in histologic grading of MRI/US image fusion biopsy by comparing conventional 12-core TRUS-Bx at radical prostatectomy specimens (RP). Methods: Consecutive patients diagnosed prostate cancer (127 with combination of both targeted biopsy (TBx) plus systematic biopsies (SBx) and separate patient cohort of 330 conventional TRUS-Bx without mpMRI) with a PSA level of <20 ng/mL prior to RP were included. The primary end point was the grade group concordance between biopsy and RP pathology according to biopsy technique. Results: Clinically significant prostate cancer detection was 51.2% for TRUS-Bx, 49.5% for SBx, 67% for TBx and 75.7% for TBx + SBx. Upgrading and downgrading of at least one Gleason Grade Group (GGG) was recorded in 43.3%/ 6.7% patients of the TRUS-Bx and in 20.5%/ 22% of the TBX + SBx group, respectively (all P <.001). Concordance level was detected to be significantly higher for ISUP 1 in combined TBx + SBx method compared to conventional TRUS-Bx (61.3% vs 37.9%, P =.014). In ISUP 1 exclusively, significant upgrading was seen in TRUS-Bx (62.1%) when compared to TBx (41.4%) and TBx + SBx (38.7%). Conclusions: MRI-targeted biopsies detected more significant PCa than TRUS-Bx but, superiority in significant cancer detection appears as a result of inadvertant selective sampling of small higher grade areas. Within an otherwise low grade cancer and does not reflect accurate GGG final surgical pathology. TBx + SBx has the greatest concordance in ISUP Grade 1 with less upgrading which is utmost important for active surveillance.
Keywords: ACTIVE SURVEILLANCE; GLEASON SCORE; GRADING SYSTEM; CANCER; ACCURACY; OUTCOMES